A Spore massage? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Writing from Abomey in Benin, Romuald Atrevy tells us of some side effects of reading Spore.You can take Spore anywhere : it's light and easy to carry. It has helped us to persuade people unaware of the ill-effects of Aspergillus flavus on humans...